Emergence of god's favorite metallic element: Magnesium based materials for engineering and biomedical applications. (2021) - Sankaranarayanan, S.; Gupta, M.
Abstract: Magnesium is one of the most abundant and non-toxic element that is required for the sustenance of good health of livings (plants and animals) and assists in good health of planet earth due to its extremely low density when compared in aluminum, titanium and steels. Rightly, it can be called as God's favorite metallic element. Magnesium, being the lightest structural metal is an excellent choice for weight critical applications. Automobile and aerospace industries consider its utilization in engines, transmission casings, seat frames, chassis, and interior parts for fuel energy savings. The bioresorbable nature of Mg makes it suitable for temporary implants in different parts of body. However, there are concerns related to the poor mechanical properties, flammability, and corrosion resistance of Mg. To alleviate these concerns, novel Mg materials with improved properties are being developed. In view of this, an attempt is made here to summarize the key highlights and the fundamentals of Mg research related to engineering and biomedical applications.